Study of Spiritual Head and Major Departments Under Kashag of Buddhist Government in Exile in India - Nikesh Sharma; Vinod Sharma (East Asian Journal of Multidisciplinary Research, 2022)
This paper attempts to describe about Buddhism from what has been learned in the different religions in different sessions. It presents an introduction to Budhist spiritual head, major departments under Kashag and institutional departments of Budhist Government in Exile in India. His Holiness the 14h Dalai Lama, Tenzin Gyatso, is the head of state and the spiritual leader of the Tibetan people. On 10 December, 1989, his Holiness was awarded with the Noble peace Prize. Furthermore it will discuss the spread of Buddhism and the diverse sects that developed in South and East Asia including some of their core beliefs and practices. The discourse will then jump to Buddhism present in the western world, specifically in the United States. The Kashag (Cabinet) is the apex executive organ of the Central Tibetan Administration and its members are ministers of the CTA. The Charter of the Tibetans in Exile stipulates that the Kashag should have a maximum of eight members.